Effect of V₂O₅ and Sb₂O₃ doping on the microstructure, electrical properties and DC degradation behavior of ZnO-Bi ₂O₃-MnO ₂ low voltage varistor ceramics - Umar, Dahiru (2016)
There is a need to enhance the nonlinear coefficient (α) of low varistor ceramic by substituting V2O5 instead of the usual Bi2O3 as a liquid sintering aid and improve the stability against DC-thermal stress. Therefore in this study, the first aim to study the effect of small intervals of sintering temperatures on the microstructure and electrical properties of V2O5 doped ZnO-Bi2O3-Sb2O3-MnO2 varistor ceramics and secondly, to evaluate the stability of ZnO-Bi2O3-MnO2 varistor ceramics doped with V2O5 and Sb2O3 against DC-thermal stress. To achieve these objectives the materials were divided into three systems System 1 (98.3 – x) ZnO, xV2O5, 0.7Bi2O3, 0.3Sb2O3, 0.7MnO2; for x = 0 mol%, system 2 (98.3 – x) ZnO, xV2O5, 0.7Bi2O3, 0.3Sb2O3, 0.7 MnO2; for x = 0.08 to 0.4 mol%, and system 3 (98.4 – y) ZnO, 0.2V2O5, ySb2O3, 0.7Bi2O3, 0.7MnO2; for y = 0 to 1 mol%. The constituent raw powders were weighed according to their weight proportion and then process via solid state reaction technique. The J-E characteristics of the sintered ceramics were measured at a room temperature by means of a source measure unit. The morphology of varistor ceramic samples was investigated via XRD SEM and EDX. The stability was investigated by subjecting the samples at 120 °C and DC thermal stress for a period of 18 hours. The XRD analysis shows the presence of two main phases of ZnO and MnO2 in system 1 and 2, another phase, including spinel and polymorphs secondary phase is related to V, Bi, Sb and Mn species. The SEM and EDX results show the microstructure and the presence of all the elements used. It was found that V2O5 improved the varistor ceramic microstructure through densification and grain boundary enhancement. In system 1, the density decreased with the increase in sintering temperature (from 1200 to 1300°C) for ZBSM varistor ceramics. When doping 0.2 mol% V2O5 the varistor ceramic had the optimum α and the grain boundary enhances (system 2). However, at a fixed 0.2 V2O5 and varying Sb2O3 on ZVBM varistor ceramics. The average grain size increase with the increase in sintering temperature, this was also observed for samples containing an x mol % Sb2O3 (system 3). In DC and thermal stress experiment (system 3), the undoped ceramics sintered between 1200-1300 °C are found to have low stability with Kt value 8.82×10-6 mAh-1/2 and α decreases after the stress test. Subsequently, the stability of the doped samples containing Sb2O3 improves to Kt value of 5.8×10-7 mAh-1/2 for sample with 0.6 mol% Sb2O3. The Kt improves further to 2.02×10-7 mAh-1/2 with the increase of Sb2O3 content up to 1 mol% which shows a high stability. Thus, in this study the V2O5 doping improved the varistor ceramic α which proves the hypothesis. However, 1 mol% of Sb2O3 content shows that after the DC and thermal stress varistor ceramic stability can be improved.